2011
DOI: 10.1074/jbc.m110.205781
|View full text |Cite
|
Sign up to set email alerts
|

Scapinin-induced Inhibition of Axon Elongation Is Attenuated by Phosphorylation and Translocation to the Cytoplasm

Abstract: Scapinin is an actin-and PP1-binding protein that is exclusively expressed in the brain; however, its function in neurons has not been investigated. Here we show that expression of scapinin in primary rat cortical neurons inhibits axon elongation without affecting axon branching, dendritic outgrowth, or polarity. This inhibitory effect was dependent on its ability to bind actin because a mutant form that does not bind actin had no effect on axon elongation. Immunofluorescence analysis showed that scapinin is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…2). Similarly, it has been reported that in rat cortical neurons the localization of Phactr1 does not respond to Latrunculin A or Cytochalasin D treatments (Farghaian et al, 2011). Our FRAP experiments suggested that there is continuous import of Phactr4 to the nucleus (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…2). Similarly, it has been reported that in rat cortical neurons the localization of Phactr1 does not respond to Latrunculin A or Cytochalasin D treatments (Farghaian et al, 2011). Our FRAP experiments suggested that there is continuous import of Phactr4 to the nucleus (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Thereby only extensive changes in the actin monomer pool, which cannot be corrected by simple modulation of cofilin activity, would evoke a transcriptional response. Alternatively, also other signals may contribute to the regulation, and for example both Phactr proteins (Farghaian et al, 2011) and MRTF-A (Muehlich et al, 2008) have been shown to be phosphorylated in cells. Structural studies on the Phactr4-actin complex, as well as development of methods to both measure and perturb the different stoichiometric complexes between the RPEL domain and actin, in the context of both MRTF and Phactr proteins, are required to resolve these questions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurabin-I and spinophilin are both regulatory subunits targeting PP1 to F-actin during neuronal development, which regulates spine development or axonal growth by affecting the cytoskeletal dynamics in hippocampal and cortical neurons (Bielas et al, 2007;Oliver et al, 2002). Scapinin is another PP1-inhibiting protein that inhibits axonal growth without affecting neurite branching in primary rat cortical neurons (Farghaian et al, 2011). As a regulatory subunit of PP1, IPP5 is selectively expressed in primary sensory neurons localized in the DRG.…”
Section: Ipp5 Inhibits Neurite Growth In Primary Sensory Neurons In Amentioning
confidence: 99%
“…In Phactr3, sequences required for high-affinity PP1 binding overlap its RPEL3 motif (Sagara et al, 2003), suggesting that actin and PP1 might compete for Phactr binding. Actin binding appears required for morphological changes induced by Phactr3 overexpression, and in some systems PP1 binding is also required (Sagara et al, 2009;Farghaian et al, 2011). Phactr3 inhibits PP1 activity against a model substrate (Sagara et al, 2003), but it remains unclear whether this reflects a bona fide general inhibitory function of Phactr3 or a positive function as a regulatory subunit for a different substrate (for discussion see Ceulemans and Bollen, 2004;Roy and Cyert, 2009).…”
Section: Introductionmentioning
confidence: 99%